Revealing the Molecular Mechanisms of Ozone-Induced Pulmonary Inflammatory Injury: Integrated Analysis of Metabolomics and Transcriptomics - Xiaolei Zhou; Yunnian Guo; Xiaotong Jian; Xinyi Miao; Pengpeng Wang; Xiaoke Wang; Ling Wang; Huaiyong Chen; Feifei Feng (Toxics)
O3 (ozone) is an environmental pollutant that can exacerbate inflammatory damage and contribute to respiratory diseases. However, the molecular mechanisms and potential targets for intervention in ozone-induced lung inflammatory injury are not yet known. To address this, our study exposed mice to 0.6 ppm and 1.0 ppm of O3 (3 h/d, 14 d), evaluating lung inflammation through histopathological examinations, lung function assessments, and analyses of white blood cells and inflammatory factors in BALF. Furthermore, we employed transcriptomic and non-targeted metabolomic approaches to decipher differentially expressed genes (DEGs) and metabolites in mouse lung tissue from the 1.0 ppm O3 exposure group. A comprehensive integration analysis of these omics data was conducted using Pearson correlation analysis. Finally, our findings show that ozone exposure indeed elicits pulmonary inflammation. Transcriptomic analysis identified 311 differentially expressed genes, predominantly implicated in circadian rhythm, IL-17 signaling pathway, and PPAR signaling. Meanwhile, metabolomic profiling revealed 41 differentially regulated metabolites, mainly associated with riboflavin metabolism, glutathione metabolism, and ABC transporter pathways. Integrated multi-omics analysis through Pearson correlation identified three key components (Pla2g10, O-phosphoethanolamine, and phosphorylcholine) showing significant enrichment in glycerophospholipid metabolism. Collectively, our findings suggest that glycerophospholipid metabolism may serve as potential therapeutic targets and diagnostic biomarkers for ozone-induced pulmonary inflammatory injury.